Executive Committee Minutes 2020-09-17 - Academic Senate:::::::::
Agenda amended and approved. Minutes of 9/3/2020 approved. Chair Report. President Report. Provost Report. Vice Chair Report. Request for clear guidelines and procedures on selection and removal of department chairs – postponed to next meeting. Vice President for Student Affairs Report. Associated Students Report. From SAC: Revised Negotiated Cheating and Plagiarism form – approved for Senate agenda. Vice President of Administration and Finance Report. From EPC: New MA in Early Childhood Education program- approved for Senate Agenda. From S&F: Revision to Standing Rule: Faculty Governance Distance Meetings- approved for Senate agenda. APARC Report. Senate Agenda approved. EPC Report. FSAC Report. SJSU resolution on AB 1460 – taken under advisement.